2013
DOI: 10.4103/0022-3859.118036
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in intensive care unit patients

Abstract: Candidemia is emerging as a significant problem in hospitalized patients, especially in ICU setups. Non-albicans Candida species are the major cause of candidemia as found in our study and few other studies in India. Multicentric studies involving many hospitals are required to know the true prevalence of candidemia and the status of antifungal drug resistance among Candida isolates in our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
3
20
2
1
Order By: Relevance
“…In our study, all strains were susceptible to amphotericin B, which is in line with the findings of some previous studies [30, 31]. However, inconsistent with this finding, several studies reported a few amphotericin B-resistant strains isolated from the patients with candidemia [32, 33].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, all strains were susceptible to amphotericin B, which is in line with the findings of some previous studies [30, 31]. However, inconsistent with this finding, several studies reported a few amphotericin B-resistant strains isolated from the patients with candidemia [32, 33].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies done in India shows prevalence rate of Candidemia varies from 0.65% to 6.9% (Giri et al, 2013;Verma et al, 2003;Sanhi et al, 2005;Deorukhkhar et al, 2012) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In North America, Northern Europe and North China, Candida albicans is followed by C. glabrata as the most common cause of candidaemia in contrast to the higher prevalence of C. parapsilosis and C. tropicalis than C. glabrata in Southern Europe and Latin America . Although C. albicans is reported as the main cause of candidaemia worldwide, several reports from India, indicated C. tropicalis as the most prevalent candidaemia‐causing species . Moreover, it has been shown that the species distribution can also vary on a regional scale and even on a local scale within the hospital …”
Section: Introductionmentioning
confidence: 99%